Essential â Mineral Balance on Growing Male Cattle - Suwandyastuti, SNO (ANIMAL PRODUCTION, 2004)
An experiment was designed to study the effect of unconventional protein source on the essential minerals balances of growing cattle.Â  The experiment had been conducted by experimental method with Completely Randomized Block Design, on twelve growing male cattle of Ongole Grade.Â  Based on the body weight, the animal trial was separated to three blocks, as the replication.Â  The tested treatment was four kind of protein sources in the ration (R):Â  R1 = kapok â seeds cakes; R2 = lamtoro â leave meals; R3 = cacao â pod meals and R4 = goatâs faeces.Â  The compose of ration was 50 percent of Elephant grass and 50 percent of concentrate (DM basis).Â  The measured variables were: the essential mineral balances i.e. Calcium, Phosphorus, Sodium, Potasium, Chlorine, Magnesium, Sulphur and Nitrogen.Â  The balance â trial was conducted by the total collection method.Â  The data was analyzed by the analysis of variance, and that of the interaction (Synergistic and antagonistic) by the Regression Analysis.Â  The result indicated that the total of essential mineral balance of each protein source or each ration on growing cattle of Ongole Grade is:Â  Cacao â pod meals = 116.09 g/day; Goatâs faeces = 111.89 g/day; lamtoro â leave meal = 84.64 g/day and Kapok â seed cake = 78.55 g/day.Â  These phenomena shown that all of the animal trial was in normal growth.Â  The strong synergistic interaction was reached by Ca Â« P (P <0.01; R2 = 0.92 â 0.98) while the weak interaction by Na Â« Cl (P > 0.05; R2 = 0.03 â 0.05).Â  Among the five couples of mineral elements of the antagonistic interaction the strong interaction was N Â® S (P < 0.01; R2 = 0.70 â 0.75), while the weak interaction was Na Â® P (P > 0.05; R2 = 0.08).Â  Based on all the variables measured, the experiment is concluded that: (1) all of the unconventional protein sources are able to improve the quality of the ration, indicated by the positive essential mineral balance on growing cattle of Ongole grade; (2) based on the total essential mineral balance, the most suitable protein source for growing cattle is cacao â pod meals; (3) the strong synergistic interaction was reached by Ca <----> P, while the antagonistic interaction was N ----> S.Â  (Animal Production 6(2): 101-109 (2004)Â Key Words: mineral, protein source, Ongole, cattle